The FireLoc Project: Identification, Positioning and Monitoring Forest Fires with Crowdsourced Data - Fonte, Cidália C. (2021)
The severity and impacts of forest fires have increased in the last years in several parts of the world, where devastating fires occur now almost every year. As these types of events are likely to increase due to climate changes, it is important to develop tools to assist authorities in the early identification and geolocation of ignitions so that they can be tackled as fast as possible. Several types of systems are currently being used, and others are under development, to automatically detect fires, based on, for example, thermal cameras and observation points; even so, the more systems available to detect these events and identify their location at an early stage, the better. This fact motivated the FireLoc project, currently under implementation, which aims to develop a system that will enable citizens to provide georeferenced data allowing the detection and geolocation of spotted fires in real time. The FireLoc system includes a dedicated app that enables citizens to report a spotted fire using their own smartphones. The app automatically collects the observer’s geolocation, a photograph of what is being observed, the orientation, and the approximate distance between the observer and the observed event. The FireLoc system stores reported data and includes functionalities for their validation, for data integration and processing to identify the location of spotted fires, as well as visualization of extracted information for several types of users, such as authorities and citizens. This paper presents the various components of the FireLoc project, the main challenges that are faced to obtain reliable geolocation of the observed events, and the results obtained with the first sets of collected data